Effects of Environmental Factors on Severity and Mortality of COVID-19 - Kifer, Domagoj; Bugada, Dario; Villar-Garcia, Judit; Gudelj, Ivan; Menni, Cristina; Sudre, Carole; Vučković, Frano; Ugrina, Ivo; Lorini, Luca F.; Posso, Margarita; Bettinelli, Silvia; Ughi, Nicola; et al. (Frontiers in Medicine, 2021)
Background Most respiratory viruses show pronounced seasonality, but for SARS-CoV-2 this still needs to be documented. Methods We examined the disease progression of COVID-19 in 6,911 patients admitted to hospitals in Europe and China. In addition, we evaluated progress of disease symptoms in 37,187 individuals reporting symptoms into the COVID Symptom Study application. Findings Meta-analysis of the mortality risk in eight European hospitals estimated odds ratios per one day increase in the admission date to be 0.981 (0.973-0.988, p<0.001) and per increase in ambient temperature of one degree Celsius to be 0.854 (0.773-0.944, p=0.007). Statistically significant decreases of comparable magnitude in median hospital stay, probability of transfer to Intensive Care Unit and need for mechanical ventilation were also observed in most, but not all hospitals. The analysis of individually reported symptoms of 37,187 individuals in the UK also showed the decrease in symptom duration and disease severity with time. Interpretation Severity of COVID-19 in Europe decreased significantly between March and May and the seasonality of COVID-19 is the most likely explanation.